Fusobacterium nucleatum triggers proinflammatory cell death via Z-DNA binding protein 1 in apical periodontitis - Hui Liu; Yuxuan Liu; Wei Fan; Bing Fan (Cell Communication and Signaling, 2022)
Abstract Background Z-DNA binding protein 1 (ZBP1) is a vital innate immune sensor that regulates inflammation during pathogen invasion. ZBP1 may contribute to pyroptosis, apoptosis and necroptosis in infectious diseases. In this study, Fusobacterium nucleatum (F. nucleatum) infection caused periapical inflammation through proinflammatory cell death and ZBP1 was involved in regulating the inflammatory activities caused by F. nucleatum infection in apical periodontitis (AP). Methods Human periapical tissues were tested by fluorescent in situ hybridization, immunohistochemical staining, immunofluorescence staining, quantitative real-time PCR (qRT‒PCR) and western blotting. F. nucleatum-infected and F. nucleatum extracellular vesicles (F. nucleatum-EVs)-treated RAW264.7 cells were used to detect the expression of inflammatory cytokines and different cell death mechanisms by qRT‒PCR and western blotting. ZBP1 expression in F. nucleatum-infected tissues and RAW264.7 cells was detected by qRT‒PCR, western blotting, and immunohistochemical and immunofluorescence staining. Furthermore, the expression of ZBP1 was inhibited by siRNA and different cell death pathways, including pyroptosis, apoptosis, and necroptosis, and inflammatory cytokines were measured in F. nucleatum-infected RAW264.7 cells. Results F. nucleatum was detected in AP tissues. F. nucleatum-infected RAW264.7 cells polarized to the M1 phenotype, and this was accompanied by inflammatory cytokine production. High levels of ZBP1 and GSDME (gasdermin E)-mediated pyroptosis, caspase-3-mediated apoptosis and MLKL-mediated necroptosis (PANoptosis) were identified in F. nucleatum-infected tissues and RAW264.7 cells. ZBP1 inhibition reduced inflammatory cytokine secretion and the occurrence of PANoptosis. Conclusion The present study identified a previously unknown role of ZBP1 in regulating F. nucleatum-induced proinflammatory cell death and inflammatory activation. Video abstract